(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The overall Goal of this research is to inspect the outcome of virtual reality in Post Partum Psychosis. This research targets to investigate the Virtual Reality (VR) technology which currently is being used for the treatment of depression and anxiety in Post Partum Psychosis. In recent years, it is becoming an fascinating substitute method for the treatment of Post Partum Psychosis. Post Partum Psychosis happens in approximately 2 out of every 1000 Women after childbirth. Despite the fact that it is a very rare disease, the study shows that the female felt immense panic, disinterest, incapacity to look after the child. The use of Virtual Reality (VR) is very beneficial in treating Post Partum Psychosis.